Case Study of the Impact of Using Artificial Intelligence With Cloud Computing in Smart Factory Management - ALDARABSEH, ESRAA AL (İstanbul Kültür Üniversitesi, 2022)
By employing artificial intelligence within the work of the cloud, the promised future is to create self-lead computers. Sharing the resources increased the innovation, it allows to develop of industries with high performance in the lowest time of study and analyze it quickly. This study tries to investigate the effect of the cloud on factory management that affects artificial intelligence devices that leads to the development of business growth which in affect increase the profits. Also, this research examines the factors from SWOT/PESTEL analysis among a cloud provider and consumer. Besides, linear regression is used to measure the most influential revenue of the main products in the total profit of the firm and propose a model to maximize it. The factors determined that may affect SOWT/PESTEL analysis and by brainstorming the ideas gathered and generated. Linear regression was used based on seven variables; six main revenues and total profit then applied Minitab software to obtain a relation between them. The influencer product was used to maximize its profit by Solver software. The outcomes presented an important relationship between the variables under a framework. The study presented economic growth in the firm that used cloud with AI equipment and the results proved to increase the net profit after the framework was developed.
Akıllı Fabrika Yönetiminde Bulut Bilgisayarla Yapay Zeka Kullanımının Etkisine İlişkin Vaka Çalışması
▪ Yüksek lisans tezi.
Keywords: Artificial Intelligence; Cloud; Smart Factory